A Case of Successful Pregnancy in a Complete Bicornuate Uterus - Behnaz Souvizi; Reza Jafarzadeh Esfehani (Mashhad University of Medical Sciences, 2016)
Complete bicornuate uterus is a type of Mullerian duct deformity, resulting from abnormal duct fusion. Similar to other Mullerian anomalies, bicornuate uterus is associated with specific complications during possible pregnancies. While various studies have reported successful deliveries in a bicornuate uterus, it might be accompanied with various complications, ranging from preterm labor to more catastrophic outcomes such as uterine rupture. One of the current approaches to diagnose this abnormality is ultrasound monitoring. In the present report, we presented a 25-years-old multiparous women with a history of abortion. The patient was not diagnosed with a complete bicornuate uterus in her first unsuccessful pregnancy. However, she was suspected with a complete bicornuate uterus based on the findings of ultrasound in the present pregnancy. A successful cesarean section was performed on the subject in the 39th week of gestation. According to the results, successful delivery could be achieved in patients with bicornuate uterous. Considering factors such as recurrent miscarriage, suspicious findings, and unreliable results of ultrasound, other diagnostic evaluations, including magnetic resonance imaging and hysterosalpingography, are recommended.